Realizacja polityk publicznych przez administrację publiczną - Izdebski, Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The contemporary public administration is engaged in implementation of the tasks that are the part of the public politics aiming to solve the complex social problems. The manner of creating and achieving each of the public politics is a challenge for the public administration entities. The complexity of the functions entrusted to the public administration entities in the implementation of the public politics causes the necessity of the correct recognition of those politics in the legal basis of the functioning of the public administration, in particular in the legal forms of acting by the public administration and the way of recognizing the competences of the public administration bodies regulated in the substantive administrative law. The indicated dependences cause a necessity to cooperate between the scientific disciplines that implement in the broad scope the state’s tasks and the functioning of the public administration.